Optimalisasi Pelestarian Lingkungan melalui Kegiatan Penghijauan dengan Memanfaatkan Lahan Kosong Terbengkalai - Fitriani, Fitriani; Prasetyo, Sutrisno Aji; Musholiha, Nindya Retno; Herol, Herol; Indarwanto, Muji (Jurnal Pengabdian Pelitabangsa, 2025)
Environmental problems caused by abandoned vacant land are becoming increasingly prevalent in both urban and rural areas. Unutilized land tends to create new issues, such as the reduction of green open space, declining air quality, and deterioration of the area's visual aesthetics. This community service program aims to develop a garden design plan for an abandoned plot as an initial step to optimize land use and raise environmental awareness among residents. The program was implemented in Kelurahan Setia Mekar, Kabupaten Bekasi, using a Participatory Action Research (PAR) approach that actively involved the community from problem identification to garden design and maintenance planning. The outcome of this initiative is a landscape design intended to increase green space while enhancing the area's visual quality. In addition to physical improvements, such as expanded greenery, the program successfully fostered greater community awareness, reflected in residents’ active participation in post-program maintenance. These results indicate that community-based greening planning is a strategic approach to utilizing vacant land and can be replicated in other areas with similar characteristics.